Youth preference in generation plan (GenRe) program viewed from characteristics and access to information in Padang City - Fajria, Lili; Yeni, Fitra; Herman, Hermalinda (International Journal of Research in Medical Sciences, 2018)
Background: Future planning for teenagers is an important thing that needs to be prepared to the fullest extend. Generally, teenagers have not considered that it is not a necessary to think about that when they are still in education. Although everyone has different talents and interests, still, there are many teenagers who recklessly follow their peers and make a wrong decision in taking their field of study. The Government of Indonesia through the generation plan (GenRe) program attempts to direct teenagers regarding their future. The purpose of this study is to describe the preference of teenagers in generation plan (GenRe) program in terms of characteristics of teenagers and their access to information in Padang city. The results of this study can become an input in the implementation of the programs for teenagers. Methods: Analytical with cross-sectional approach was used as the research design. 249 respondents were 13-24 year-old teenagers who were taken with accidental sampling. Data were collected with questionnaires which contained demographic data questions (age, gender, education) and access to information about Generation Plan (GenRe) program. And the data analysis used Chi-Squre statistic. Results: There was a significant correlation between the characteristics of teenagers: age (p = 0.018) gender (p = 0.037) and education (p = 0,020) on youth preference in choosing generation plan (GenRe) program, while there was no connection to information access to the program, there were: the existing source of information (p = 0.077), the desire to find information with p value = 0.097 and information obtained with the value p = 0.075). Conclusions: Therefore, we expect that the socialization of generation plan (GenRe) program needs to be improved and socialized more through social media for further development.